3rd Borneo Research Education Conference (BREC) 2015 - Joseph, Corina (UiTM Sarawak, 2016)
The 3rd Borneo Research Education Conference (BREC) was successfully organized on 5th and 6th November 2015 at the Centre of Postgraduate Studies, Universiti Malaysia Sabah, Kota Kinabalu. The conference was hosted by Swinburne University of Technology, Sarawak Campus and co-organized with Universiti Teknologi MARA Sarawak, Universiti Malaysia Sarawak (UNIMAS), Curtin University, Sarawak Campus and Universiti Malaysia Sabah (UMS). The theme of BREC 2015 was "Developing as a Researcher by Playing Scholarly Roles".